WRITTEN ON-LINE ASSESSMENT IN PRIMARY SCHOOL - GOLUBIȚCHI, Silvia (Acta et Commentationes, Sciences of Education, 2022)
The on-line assessment is based on the use of an electronic device, of which: computer, mobile phone, smartphone, notebook and is performed in a space where the assessor and the assessee are in different places at the time of assessment. In the on-line written assessment, students’ results are stored in the drive folder, which can be used at any time and can be performed by the teacher, student, colleagues or by an outside person or group. They can be in the form of an evaluation test, an evaluation test, e_portfolios, sms, e_ greeting card, e_ scribble.